Patterns and Predictors of Off-Label Drug Prescribing in Psychiatric Practice: A Qualitative Study - Sadia Shakeel; Shagufta Nesar; Hina Rehman; Khizra Jamil; Imran Ahsan Mallick; Muhammad Shahid Mustafa; Mudassir Anwar; Shazia Jamshed (Pharmacy, 2021)
Off-label drug prescribing (OLDP) must be based on strong scientific evidence to make sure that patients get the optimum therapeutic outcomes. Adherence to the prerequisites is determined by the physicians’ attitude and knowledge. In this context, the present study was conducted with the goal of investigating psychiatrists’ perceptions of the use of OLDP in their clinical practice. A total of 14 psychiatrists were interviewed using a semi-structured interview guide. Thematic content analysis was performed. Data saturation was achieved at the 12th interview. Six major themes and fifteen subthemes emerged from qualitative interviews. Among the major themes were knowledge and concepts about the off-label drugs, attitude and current practice of prescribing off-label drugs, and rationale of prescribing and suggestions for reducing the use of off-label drugs. Almost all of the respondents interviewed provided detailed comments concerning the OLDP concept, depicted an optimistic approach and deemed that OLDP is quite common in psychiatry. Off-label usage of benzodiazepines such as clonazepam, diazepam and lorazepam in mania, depression, and obsessive–compulsive disorder were commonly reported. It was observed that the majority of the respondents did not inform the patients before prescribing off-label drugs. The present findings revealed that respondents had awareness; however, they depicted diverse attitudes towards prescribing off-label drugs. Further education and sensitization in regions with impoverished knowledge would certainly assist in preventing the risks associated with the use of OLDP.